2018
DOI: 10.1007/s00024-018-2065-9
|View full text |Cite
|
Sign up to set email alerts
|

Insights on the Source of the 28 September 2018 Sulawesi Tsunami, Indonesia Based on Spectral Analyses and Numerical Simulations

Abstract: Sulawesi tsunami has been a puzzle because extreme deadly tsunami waves were generated following an Mw 7.5 strike-slip earthquake, while such earthquakes are not usually considered to produce large tsunamis. Here, we obtained, processed and analyzed two sea level records of the tsunami in the near-field (Pantoloan located inside the Palu Bay) and far-field (Mamuju located outside the Palu Bay) and conducted numerical simulations to shed light on the tsunami source. The two tide gauges recorded maximum tsunami … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

6
67
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
4
3
2

Relationship

1
8

Authors

Journals

citations
Cited by 148 publications
(82 citation statements)
references
References 34 publications
6
67
0
Order By: Relevance
“…For comparison, we also used the JAGURS model to simulate the propagation of a tsunami generated by the earthquake alone. Vertical fluctuations due to horizontal motions on steep slopes were not quantitatively large (Heidarzadeh et al 2019) and are omitted here. Because the local sea level was about 1 m higher than mean sea level at the time of the earthquake ( Fig.…”
Section: Conditions Of Tsunami Calculationmentioning
confidence: 99%
See 1 more Smart Citation
“…For comparison, we also used the JAGURS model to simulate the propagation of a tsunami generated by the earthquake alone. Vertical fluctuations due to horizontal motions on steep slopes were not quantitatively large (Heidarzadeh et al 2019) and are omitted here. Because the local sea level was about 1 m higher than mean sea level at the time of the earthquake ( Fig.…”
Section: Conditions Of Tsunami Calculationmentioning
confidence: 99%
“…Various tsunami sources have been modeled based on seismic data [Heidarzadeh et al (2019), using data from USGS (2018), Ulrich et al (2019)], Sentinel-2 satellite optical data (Jamelot et al 2019), Sentinel-1 satellite SAR images (Gusman et al 2019), and hypothetical submarine landslides (Pakoksung et al 2019). Although those studies compared calculated tsunami waveforms with the Pantoloan tide gauge record and tsunami heights determined by field surveys, a detailed comparison with tsunami heights over the entire bay has not been performed except for Ulrich et al (2019), and little quantitative consideration has been given to the video footage.…”
Section: Introductionmentioning
confidence: 99%
“…Bathymetry of the Java Sea has been generated using gridded national bathymetry of Indonesia (BATNAS) provided from the Geospatial Information Agency (we referred to BIG: 'Badan Informasi Geospasial' in Indonesian) (http://tides.big.go.id/DEMNAS/) within a 6 arc-second resolution. This data has been produced through the inversion of gravity anomaly of altimetry by adding sounding data carried with single and multi-beam surveys, which has better resolution in coastal areas than GEBCO (30 arc-second) [44,45]. Land topography data was resolved using the DEMNAS (0.27 arc-second resolution) also from BIG.…”
Section: Data Acquisitionmentioning
confidence: 99%
“…A single straight fault with the same orientation was also used in a joint inversion for the fault slip constrained with InSAR and optical imagery data (Socquet et al, 2019). These results and slip models from other researchers have been used to estimate the coseismic seafloor deformation and the corresponding initial tsunami surface elevation (e.g., Heidarzadeh et al, 2019) however, the tsunami simulations underestimate the runup heights reported in the post-tsunami surveys (Fritz et al, 2018;Omira et al, 2019). As a result, the exact geometry of the faults beneath the bay became critically important to understanding the tsunami source mechanism.…”
Section: Introductionmentioning
confidence: 99%